2016
DOI: 10.1021/acs.jafc.6b00087
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Induced Soluble Protein Aggregates from Mixed Pea Globulins and β-Lactoglobulin

Abstract: The present work investigates the formation of protein aggregates (85 °C, 60 min incubation) upon heat treatment of β-lactoglobulin (βlg)-pea globulins (Glob) mixtures at pH 7.2 and 5 mM NaCl from laboratory-prepared protein isolates. Various βlg/Glob weight ratios were applied, for a total protein concentration of 2 wt % in admixture. Different analytical methods were used to determine the aggregation behavior of "mixed" aggregates, that is, surface hydrophobicity and also sulfhydryl content, protein interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 49 publications
(195 reference statements)
9
64
0
Order By: Relevance
“…Previous works have also shown that heat treatment of cowpea protein isolate at 70°C and 90°C (Peyrano et al, 2016) or whey proteins at 72°C and 140°C (Patel, Singh, Anema, & Creamer, 2004) did not produce changes in the polypeptide patterns after SDS-ME PAGE analysis. However, some of the proteins extracted by the SDS-ME buffer were too large to enter the gel as shown by the band at the origin (top of gel), which corroborates the data from native-PAGE and is consistent with previous reports (Chihi, Mession, Sok, & Saurel, 2016;Mession, Sok, Assifaoui, & Saurel, 2013;Shand et al, 2007).…”
Section: Polyacrylamide Gel Electrophoresissupporting
confidence: 91%
“…Previous works have also shown that heat treatment of cowpea protein isolate at 70°C and 90°C (Peyrano et al, 2016) or whey proteins at 72°C and 140°C (Patel, Singh, Anema, & Creamer, 2004) did not produce changes in the polypeptide patterns after SDS-ME PAGE analysis. However, some of the proteins extracted by the SDS-ME buffer were too large to enter the gel as shown by the band at the origin (top of gel), which corroborates the data from native-PAGE and is consistent with previous reports (Chihi, Mession, Sok, & Saurel, 2016;Mession, Sok, Assifaoui, & Saurel, 2013;Shand et al, 2007).…”
Section: Polyacrylamide Gel Electrophoresissupporting
confidence: 91%
“…Whatever the pH studied, the thermal treatment led to increase significantly H o of the albumin protein particles, about one‐and‐half times as compared with NA. The thermal treatment caused the exposition of hydrophobic groups initially buried in the structure of NA molecules, resulting in an increase in surface hydrophobicity in accordance with the general behavior of globular proteins (Chihi et al., ).…”
Section: Resultsmentioning
confidence: 73%
“…Whatever the pH studied, the thermal treatment led to increase significantly H o of the albumin protein particles, about one-andhalf times as compared with NA. The thermal treatment caused the exposition of hydrophobic groups initially buried in the structure of NA molecules, resulting in an increase in surface hydrophobicity in accordance with the general behavior of globular proteins (Chihi et al, 2016 It is important to note that the present determination of H o was done from protein samples containing soluble and insoluble fractions of aggregates in order to be representative of the protein material used for foam preparation.…”
Section: Surface Hydrophobicitymentioning
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, the mechanism of such aggregate formation for soluble MnP still needs further study. Chihi et al [54] demonstrated that the hydrophobic interactions and the formation of new disulfide bridges resulted in soluble protein aggregates; while, Wang et al [55] emphasized the importance of the hydrophobic interaction in promoting the protein aggregate, as compared with disulfide bonds. Therefore, we will shed light on the intriguing mechanism of polymerization for soluble MnP in the future.…”
Section: Discussionmentioning
confidence: 99%